2011
DOI: 10.1186/1471-2407-11-491
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to statins restricts human tumour growth in Nude mice

Abstract: BackgroundStatins have long been used as anti-hypercholesterolemia drugs, but numerous lines of evidence suggest that they may also bear anti-tumour potential. We have recently demonstrated that it was possible to isolate cancer cells adapted to growth in the continuous presence of lovastatin. These cells grew more slowly than the statin-sensitive cells of origin. In the present study, we compared the ability of both statin-sensitive and statin-resistant cells to give rise to tumours in Nude mice.MethodsHGT-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In addition, lovastatin induced procaspase--7 in a transcriptional manner, as it did for caspase--2 in other digestive cell lines [64], indicating that these caspases could be important drivers of the cytotoxic response elicited in cancer cells. Furthermore, statin--adapted HGT--1 cells grew more slowly in vitro and in vivo when transplanted into immuno--compromised mice, suggesting that adaptation to statins could lower tumor growth in this model [65].…”
Section: 22--gastric Cancermentioning
confidence: 97%
“…In addition, lovastatin induced procaspase--7 in a transcriptional manner, as it did for caspase--2 in other digestive cell lines [64], indicating that these caspases could be important drivers of the cytotoxic response elicited in cancer cells. Furthermore, statin--adapted HGT--1 cells grew more slowly in vitro and in vivo when transplanted into immuno--compromised mice, suggesting that adaptation to statins could lower tumor growth in this model [65].…”
Section: 22--gastric Cancermentioning
confidence: 97%
“…160,161 In a 3D glioblastoma model, exosomes generated from human endometrial stem cells harboring the apoptotic drug atorvastatin, which inhibits cancer growth through a variety of mechanisms, dramatically reduced tumor growth. [162][163][164] A number of researchers have looked into the possibility and mechanism of exosomal surface changes. Surface adjustments are implemented to exosomal surface proteins and functional groups.…”
Section: Nanotechnology Platforms For Brain Cancer Drug Deliverymentioning
confidence: 99%
“…To investigate the direct relationship between statins and anti-cancer activity, its effect on several types of cancers has been analyzed [ 91 ]. The results showed that statins induce cancer cell death by triggering the apoptotic pathway, not only in cell models but also in murine GC xenografts [ 92 , 93 ]. These findings suggest that statins may possess anti-cancer activity; however, very few clinical studies have reported that statins are anti-cancer drugs.…”
Section: Statin Use Reduces Gc Riskmentioning
confidence: 99%